Allocation of battery energy storage in power distribution network: Placement, sizing, and scheduling. Issue 3 (14th September 2022) - Kayal, Partha; Kumar, Bablu; Samantary, Soumyakanta
ABSTRACT: The present power distribution infrastructure faces significantly high demand in most of the time hours of the day. Thus, it needs to manage power intelligently in those high-demand hours. Optimal allocation of battery energy storage system (BESS) can foster power management in the distribution system by exchanging energy with it. However, BESS should be strategically allocated to achieve maximum power delivery efficiency with lower investment. BESS units also need to be strategically scheduled to charge in light load hours and discharged in peak demand hours. The present study proposes a strategic planning model that can minimize the cost of BESS allocation and improve the distribution network's technical performance. The cost function is framed considering battery life, investment in BESS, and investment in the inverter. The distribution system's performance is realized with a typical network performance index (NPI). The NPI is synthesized from voltage deviation of buses and change in total active power losses in the network. A multiobjective optimization algorithm-based solution technique is presented to comprehend the planning model's outcome in the most suitable location, size, and battery scheduling scenario. The proposed planning approach has been tested on a 28-bus Indian power distribution network. The result of techno-economic optimization confirms a good trade-off solution with 37.5% of network performance improvement with respect to the base configuration and INR 39.06LAC of total investment. The proposed approach has been verified with the existing BESS allocation model, demonstrating its efficacy.